2015
DOI: 10.1038/ejcn.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vitamin E supplementation on serum C-reactive protein level: a meta-analysis of randomized controlled trials

Abstract: C-reactive protein (CRP), a marker of chronic inflammation, has a major role in the etiology of chronic disease. Vitamin E may have anti-inflammatory effects. However, there is no consensus on the effects of vitamin E supplementation on CRP levels in clinical trials. The aim of this study was to systematically review randomized controlled trials (RCTs) that report on the effects of vitamin E supplementation (α- and γ-tocopherols) on CRP levels. A systematic search of RCTs was conducted on Medline and EMBASE th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(50 citation statements)
references
References 46 publications
1
44
1
4
Order By: Relevance
“…Moreover, MMN supplementation interacted with maternal biomarkers PC at baseline to influence biomarkers PC at post-supplementation. Previous studies have reported that vitamin C and E supplementation reduced CRP concentrations [36,46], and vitamin D influenced serum leptin and adiponectin concentrations [47].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, MMN supplementation interacted with maternal biomarkers PC at baseline to influence biomarkers PC at post-supplementation. Previous studies have reported that vitamin C and E supplementation reduced CRP concentrations [36,46], and vitamin D influenced serum leptin and adiponectin concentrations [47].…”
Section: Discussionmentioning
confidence: 99%
“…These findings confirm that inflammatory mechanisms may be involved in the pathogenesis of CIAKI incidence. It may be speculated that the effects of vitamin E are applied, in some part, through attenuation of inflammation in addition to scavenging free oxygen radicals . A recent meta‐analysis that evaluated the effects of vitamin E–coated dialyzer on oxidative status and inflammation revealed that dialyzer membrane containing vitamin E decreased inflammatory markers, reflecting the anti‐inflammatory property of vitamin E …”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 2, α-TOH is also connected with C-reactive protein (CRP, P02741), which is a marker of inflammation. Several previous studies have shown the anti-inflammatory effect of α-TOH [26,27] and indicated a biological relationship between these two proteins. These examples show that MOTA has a promising capability to pinpoint disrupted regulatory relationships between biomolecules by a pathophysiological condition and highlight important risk molecules.…”
Section: Ranking Disease-associated Metabolitesmentioning
confidence: 92%